2017
DOI: 10.1002/advs.201600502
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Host Material for Long‐Lifespan Blue Organic Light‐Emitting Diodes Using Thermally Activated Delayed Fluorescence

Abstract: It has been challenging to find stable blue organic light emitting diodes (OLEDs) that rely on thermally activated delayed fluorescence (TADF). Lack of stable host materials well‐fitted to the TADF emitters is one of the critical reasons. The most popular host for blue TADF, bis[2‐(diphenylphosphino)phenyl] ether oxide (DPEPO), leads to unrealistically high maximum external quantum efficiency. DPEPO is however an unstable material and has a poor charge transporting ability, which in turn induces an intrinsic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 27 publications
3
123
0
Order By: Relevance
“…As one of the few articles claiming a reasonable device lifespan when using a blue TADF emitter, there is significant room for additional research aimed at increasing the lifetime and EQE at practical luminance; the efficiency of a device using DDCzTrz in mCBP host was likely less than 2% at the luminance of 500 cd m −2 . Cho et al reported an alkyl‐free 2,3,4,5,6‐penta(9 H ‐carbazol‐9‐yl)benzonitrile (5CzCN) TADF blue emitter that was feasible for both vacuum evaporation and solution spin‐coating techniques and exhibited EQE max values of 19.7% and 18.7%, respectively .…”
Section: Operational Stability Of Blue Tadf‐oledsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the few articles claiming a reasonable device lifespan when using a blue TADF emitter, there is significant room for additional research aimed at increasing the lifetime and EQE at practical luminance; the efficiency of a device using DDCzTrz in mCBP host was likely less than 2% at the luminance of 500 cd m −2 . Cho et al reported an alkyl‐free 2,3,4,5,6‐penta(9 H ‐carbazol‐9‐yl)benzonitrile (5CzCN) TADF blue emitter that was feasible for both vacuum evaporation and solution spin‐coating techniques and exhibited EQE max values of 19.7% and 18.7%, respectively .…”
Section: Operational Stability Of Blue Tadf‐oledsmentioning
confidence: 99%
“…The lack of stable host materials that are suited to the TADF emitter hinders the prospect of realizing stable blue TADF‐OLEDs. Kim et al reported a novel compound by modifying mCBP into 3′,5‐di(9 H ‐carbazol‐9‐yl)‐[1,1′‐biphenyl]‐3‐carbonitrile (mCBP‐CN) to serve as an alternative host to replace the popular DPEPO ( Figure ). A blue TADF‐OLED developed using this host exhibited an EQE of 8.7% with LT 80 of 21 h at the initial luminance of 500 cd m −2 using 5,8‐bis(4‐(2,6‐diphenylpyrimidin‐4‐yl)phenyl)‐5,8‐dihydroindolo[2,3‐c]carba‐zole (BDpyInCz) as the blue dopant .…”
Section: Operational Stability Of Blue Tadf‐oledsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, fewer studies have been reported on the long operational lifetime of blue TADF‐OLEDs. [ 18–22 ] S. G. Ihn et al reported indolocarbazole and pyrimidine‐based TADF emitter, 5,8‐bis(4‐(2,6‐diphenylpyrimidin‐4‐yl)phenyl)‐5,8‐dihydroindolo[2,3‐c]carbazole (BDpyInCz) with a long‐delayed exciton lifetime of 32 µs. [ 18 ] However, their device exhibited a low external quantum efficiency (EQE) (12%) and device lifetime (LT 80 ) of only 8 h at the initial luminance of 500 cd m −2 with deep‐blue color coordinates of (0.16, 0.20).…”
Section: Introductionmentioning
confidence: 99%
“…[8]. Use of improper host may lead to worthless recombination outside the emissive layer, unbalanced charge transport and charge leakage at the interface of electrodes [9][10].…”
Section: Introductionmentioning
confidence: 99%